Pengaruh Kualitas Produk, Promosi, dan E-WOM Terhadap Keputusan Pembelian Viva Cosmetics di Kota Batam - Sherent Sherent; Alice Erni Husein (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study was designed to examine the influence of product quality, promotional activities, and e-WOM on the formation of purchasing decisions for Viva Cosmetics products in Batam City. The research design used a descriptive quantitative approach that aims to describe the causal relationship between variables through objective measurements. The study involved 100 respondents who were users and buyers of Viva Cosmetics, with the sample selection technique being purposive sampling according to predetermined criteria and strengthened through Lemeshow calculations to ensure sample adequacy. The research data were analyzed through several statistical stages, including instrument feasibility testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing to determine the level of contribution of each independent variable to purchasing decisions. The findings from the multiple linear regression analysis showed that product quality contributed 19.1% to purchasing decisions. Furthermore, promotions contributed 24.0%, and e-WOM contributed 37.2%. The results of the coefficient of determination (R²) test indicate that a value of 83.7% reflects the ability of the product quality, promotion, and e-WOM variables simultaneously to explain the majority of changes in Viva Cosmetics purchasing decisions in Batam City. The results of the t-test and F-test can conclude that these three variables have a significant role, both individually and collectively, in influencing the purchasing decisions of Viva Cosmetics products in Batam City.